Lexical Peculiarities of British Blogs - VARLAMOVA, ELENA VALERIEVNA; KORNILOVA, DARYA DMITRIEVNA; SAFONKINA, OLGA SERGEEVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This work is devoted to identify the specifics of lexical component of texts in the Internet discourse and study the general pattern in creating an English-language blog. The relevance of this study lies in the fact that lexical features and their functions are comprehensively studied in the popularized sphere of the Internet. The purpose is to analyze and compare the lexical characteristics of English texts, identify their interconnection and significance in the design of the blog, as well as, applying to concrete examples, by using a consistent analysis algorithm based on material of the British site British Library Blogs.RESUMEN El trabajo presentado está dedicado a identificar los detalles del componente léxico de los textos en el discurso de Internet y estudiar el patrón general en la creación de un blog en inglés. La relevancia de este estudio radica en el hecho de que las características léxicas y sus funciones se estudian exhaustivamente en la esfera popularizada de Internet. El propósito es analizar y comparar las características léxicas de los textos en inglés, identificar su interconexión y significado en el diseño del blog, así como también aplicar a ejemplos concretos, usando un algoritmo de análisis consistente basado en material del sitio británico Blogs de la Biblioteca Británica.